A Compct 5.8 GHz CPW Double Square Edge Antenna With BPF Stepped Impedance Resonator - Mujahidin, Irfan (Program Studi Teknik Elektro Universitas Khairun, 2020)
This research proposes a 5.8 GHz circular polarization double square edge antenna with a bandpass filter that used a method stepped impedance resonator (BPF-SIR) structure for designing a compact integrated antenna with the filter. the double layer electromagnetic circuit structure is used to miniaturize antenna integrated with complex bandpass filter at 5.8 GHz frequency operation. furthermore, a novel electromagnetic component has been developed to produce a 5.8 GHz antenna with good gain value. even this circuit have not complex configuration, and inexpensive material, especially for the premium-frequency.